2000
DOI: 10.1038/sj.onc.1203266
|View full text |Cite
|
Sign up to set email alerts
|

Heritable lympho-epithelial thymoma resulting from a transgene insertional mutation

Abstract: Thymoma is the most common tumor of the anteriorsuperior mediastinum. We have identi®ed a line of transgenic mice which spontaneously and heritably develop thymomas at a very high penetrance. The available data suggest that thymoma formation in these mice results as a consequence of transgene insertional mutagenesis. Immune histologic analyses indicate that the thymomas are of epithelial cell origin. Survival studies indicate that tumor progression is more aggressive in females as compared to males (73.9 vs 41… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 16 publications
0
14
1
Order By: Relevance
“…Additionally, males had slightly higher thymoma risk than females. Animal models of thymoma offer conflicting evidence on the importance of sex and reproductive hormones 18, 19. We did not find significantly elevated (or reduced) risk for tumors of reproductive organs among thymoma patients, arguing against a role for hormonal factors.…”
Section: Discussioncontrasting
confidence: 66%
“…Additionally, males had slightly higher thymoma risk than females. Animal models of thymoma offer conflicting evidence on the importance of sex and reproductive hormones 18, 19. We did not find significantly elevated (or reduced) risk for tumors of reproductive organs among thymoma patients, arguing against a role for hormonal factors.…”
Section: Discussioncontrasting
confidence: 66%
“…Translocation encompassing the analogous region in humans has been implicated in lymphoepithelial thymoma. 19 Spontaneous cases of human type B3 and type C thymomas showed chromosomal imbalances, with a gain in various chromosome segments or loss of entire chromosomes. Type A thymomas did not reveal chromosomal gains or losses.…”
Section: Discussionmentioning
confidence: 99%
“…1998). Recently, Nakajima et al . (2000) demonstrated that heritable lympho‐epithelial thymoma was induced in a line of transgenic mice by insertional mutation of a transgene.…”
Section: Discussionmentioning
confidence: 99%